School climate, gender, and burnout among public secondary school teachers in Selangor - Abd Rahman, Anis Farahanim; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Teachers’ welfare should be taken into consideration due to the rise in reported cases of mental illness among school teachers, which later lead to the wrong perception of teaching profession as the most stressful profession. Factors that contributed towards burnout among school teachers need to be found out. Previous studies that have been reviewed provided clearer understanding on the factors that have caused burnout among school teachers. This research is focusing in identifying the climate and burnout profile of public secondary school in Selangor and also to identify differences in burnout experience between male and female teachers. This research applied descriptive research design that involved 258 public secondary school teachers that have been selected from around Selangor. Instruments that have been used in measuring variables in this research are The Effective School Battery – Teacher Inventory (to measure school climate), Big Five Inventory (to measure personality types), and Copenhagen Burnout Inventory (to measure burnout). Research data was analyzed by using descriptive statistics. Analysis that has been done showed that most of the schools in Selangor are having positive school climate. In general, it can be seen that teachers are experiencing moderate burnout. In relation to gender, analysis that has been done showed that female teachers experience more burnout as compared to male teachers. Findings from this paper may be useful to increase the understanding on factors that contribute towards burnout among school teachers and for the development of future intervention that will help to reduce the occurrence of burnout among teachers.